Study on Feebly Local Function - Yousif Jaafar Al-Fahham, Afeefa; Kadham Altalkany, Yiezi (International Journal of Engineering and Technology, 2018)
A new type of local function in ideal topological spaces was submitted with some theorems and relations between the new type of local function and other typesÂ